Analyzing barriers for the adoption of circular economy in the manufacturing sector. Issue 3 (3rd June 2021) - Badhotiya, Gaurav Kumar; Avikal, Shwetank; Soni, Gunjan; Sengar, Neeraj
Abstract : Purpose: The operational activities of manufacturing organizations are continuously degrading the environment. Circular economy adoption can help industries optimize their resources along with minimal waste generation. The purpose of this study is to identify and analyze the barriers that hinder the adoption of circular economy (CE) in the manufacturing sector. Design/methodology/approach: The barriers are extracted from a critical review of the literature and listed into three categories as social, economic and environmental. The barriers in each category are then analyzed using the fuzzy-based analytic hierarchy process method. The approach is capable to consider the fuzziness in the preference of barriers and determine their priority. Findings: The pairwise comparison and weight of all the main and sub-criteria are computed, which helps in deciding the ranking of barriers. The results show that social criteria are having the highest importance followed by economic and environmental criteria. Among all the sub-criteria, low demand and acceptance of remanufactured products is at the highest level followed by lack of government support and legislation barrier. Originality/value: The outcome of this study would be helpful for the decision makers and business managers in the manufacturing sector to focus on the barriers in each category and accordingly formulate strategies for CE adoption.